2011
DOI: 10.1152/ajpcell.00385.2010
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular purine metabolism and signaling of CD73-derived adenosine in murine Treg and Teff cells

Abstract: CD73-derived adenosine acts as potent inhibitor of inflammation, and regulatory T cells (Treg) have been shown to express CD73 as a novel marker. This study explored the role of endogenously formed adenosine in modulating NF-κB activity and cytokine/chemokine release from murine Treg and effector T cells (Teff) including key enzymes/purinergic receptors of extracellular ATP catabolism. Stimulating murine splenocytes and CD4(+) T cells with anti-CD3/anti-CD28 significantly upregulated activated NF-κB in CD73(-/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
111
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 48 publications
6
111
0
1
Order By: Relevance
“…11 A recent study reported that stimulation of the A 2A R during antigen-dependent stimulation enhanced FoxP3 and LAG-3 expression in T cells. 20 In our study, we compared gene expression of known Treg functional molecules in freshly isolated CD4 + CD25 + Tregs from WT and A 2A R KO mice (including FoxP3, IL-10, TGF-b1, CTLA-4, CD73, CD39, or LAG-3) and found no difference in Tregs between the two genotypes of mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 A recent study reported that stimulation of the A 2A R during antigen-dependent stimulation enhanced FoxP3 and LAG-3 expression in T cells. 20 In our study, we compared gene expression of known Treg functional molecules in freshly isolated CD4 + CD25 + Tregs from WT and A 2A R KO mice (including FoxP3, IL-10, TGF-b1, CTLA-4, CD73, CD39, or LAG-3) and found no difference in Tregs between the two genotypes of mice.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Adenosine generation by Tregs is a recognized mechanism of suppressing adaptive immune responses. [8][9][10]12 To investigate the requirement for adenosine generation by Tregs in suppressing the inflammation that contributes to kidney IRI, we compared the ability of adoptively transferred WTand CD73 KO Tregs to protect from kidney IRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD73 + converts AMP to adenosine, regulating the immune response [33]. Abnormal levels in these parameters may alter inflammatory reactions in the CFS/ME patients altering the extent of Treg suppression of other immune cells and immune processes [31].…”
Section: Discussionmentioning
confidence: 99%